Laser‐Patterned n‐Type Front‐Junction Silicon Solar Cell With Tantalum Oxide/Silicon Nitride Passivation and Antireflection. Issue 2 (16th January 2018) - Wan, Yimao; Hsiao, Pei‐Chieh; Zhang, Wei; Lennon, Alison; Chen, Yifeng; Feng, Zhiqiang; Verlinden, Pierre; Samundsett, Christian; Cui, Jie; Yan, Di; Cuevas, Andres
Abstract : This work demonstrates, for the first time, a tantalum oxide/silicon nitride (Ta2 O5 /SiN x ) stack as a combined passivation and antireflection coating deposited on the boron‐diffused front surface of n‐type silicon solar cells. Due to the high chemical resistance of Ta2 O5, the patterning of the films is realized via picosecond laser ablation, followed by a field‐induced metal plating of nickel and copper to form the front metal grid electrode. A solar cell conversion efficiency of 19.3% is achieved, and further improvements are anticipated from the optimization of the laser ablation process and the tuning of the thickness of the individual layers of the dielectric stack. Abstract : This work demonstrates, for the first time, a tantalum oxide/silicon nitride (Ta2 O5 /SiN x ) stack as a combined passivation and an anti‐reflection coating on n ‐ type silicon solar cells. By patterning by picosecond laser ablation and metallization via field‐induced platin, a solar cell conversion efficiency of 19.3% is achieved.